1970
DOI: 10.1016/0031-9384(70)90193-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental control of ECS-produced retrograde amnesia in goldfish

Abstract: The retrograde amnestic effect of ECS can be enhanced by exposing the goldfish to the intertrial environment for 25 mm just prior to administration of the ECS. As the interval between training and the ECS is increased, the amnesm produced by the environment-ECS interaction takes longer to develop. The environment-dependent effects of ECS relate to those of other amnestic agents which have previously been described. Amnesia Memory consolidation Shock avoidance Conditioning goldfish Electroconvulsive shock

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

1971
1971
1973
1973

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
2
13
1
Order By: Relevance
“…Aversive effects of a single ECS, as typically used in experiments on the amnestic effects of ECS in the laboratory rat have been described [21]. Stimulus effects of amnestic agents could be responsible for environment-dependent amnesia in goldfish [7]. The present demonstration that a single ECS treatment has behavioral effects which can be attributed to the stimulus properties of the treatment supports this possibility.…”
Section: Puromycin Effectssupporting
confidence: 60%
See 3 more Smart Citations
“…Aversive effects of a single ECS, as typically used in experiments on the amnestic effects of ECS in the laboratory rat have been described [21]. Stimulus effects of amnestic agents could be responsible for environment-dependent amnesia in goldfish [7]. The present demonstration that a single ECS treatment has behavioral effects which can be attributed to the stimulus properties of the treatment supports this possibility.…”
Section: Puromycin Effectssupporting
confidence: 60%
“…But we cannot rule out the possibility that the interference represents a memory loss. Memory activated during a session might be vulnerable to interference by an immediate postsession ECS [7,13,22]. We propose, however, that the present results show two effects of ECS neither of which entails a loss of memory.…”
Section: Puromycin Effectscontrasting
confidence: 59%
See 2 more Smart Citations
“…reported that ECS can produce retrograde amnesia of classically conditioned inhibition of ventilation rates (opercula beats) in cataleptic goldfish. Prior experiments in noncataleptic fish showed that ECS can induce amnesia of an active avoidance response [1,2]. That ECS can block retention of automatic and behavioral responses suggested that both types of responses could be mediated by common memory processes.…”
Section: Davis and Holmesmentioning
confidence: 99%